2004
DOI: 10.1021/jp0452103
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide Organometallic Sandwich Nanowires:  Formation Mechanism

Abstract: A molecular beam of europium-cyclooctatetraene sandwich nanowires Eu(n)()(COT)(m)() was produced by a laser vaporization synthesis method. The formation mechanism of the nanowires was quantitatively revealed by photoelectron and photoionization spectroscopies of the Eu-COT species, together with supporting theoretical calculations. From these results, it is confirmed that growth processes extending the length of Eu-COT nanowires involve a series of elementary reactions in which efficient charge transfer occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
85
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 7 publications
1
85
1
Order By: Relevance
“…Our calculations confirm that the structures of the Eu 2 C 8 H 8 3 molecule and its ionic species are sandwiches with the metal atom above the center of gravity of C 8 H 8 ligand molecules [8][9][10] anion for which the energy difference between FM and AFM magnetic states vanishes.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Our calculations confirm that the structures of the Eu 2 C 8 H 8 3 molecule and its ionic species are sandwiches with the metal atom above the center of gravity of C 8 H 8 ligand molecules [8][9][10] anion for which the energy difference between FM and AFM magnetic states vanishes.…”
supporting
confidence: 68%
“…Because of the strong aromatic character [19,20] of the orbitals located at the C 8 H 8 rings the 4f electrons are drastically shifted in energy from the low part of the valence electrons towards the Fermi level [which is placed in the middle of the highest occupied molecular orbital -lowest unoccupied molecular orbital (HOMO-LUMO) gap]. This effect has been also observed in the experiments [8,10]. The new molecular orbitals, formed in a similar manner as previously shown for other sandwich-type systems (see [17] and the references therein), accommodate the 6s as well as small fractions of 4f electrons of the Eu atoms.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Actually, very recently, Hosoya et al have reported the synthesis of Eu-COT nanowires by laser vaporisation techniques. [18] Extension to longer wires incorporating more Th(C 6 H 6 ) units is also expected to result in singlet multiplicity molecules with ten-pelectron benzene fragments. A molecular wire with an adjustable length incorporating high-electron-density C 6 H 6 units is therefore within reach.…”
Section: Full Papermentioning
confidence: 99%